Metastatic Rectal Carcinoma with Long-Term Remission due to Modern Multimodality Treatment - Eigeliene Natalja; Saarenheimo Jatta; Wichmann Viktor; Österlund Pia; Jekunen Antti (S. Karger AG, 2025)
In the era of personalized medicine, systemic treatment with chemotherapy in combination with targeted drugs, tailored according to RAS and BRAF status, has improved the survival of patients with metastatic colorectal cancer (mCRC), but curative resection of metastases provides the only chance of cure. Here, we present a 40-year-old male with rectal adenocarcinoma and multiple bilateral synchronous liver metastases who has achieved long-term remission with multimodal treatment without resection of all metastatic lesions. This case emphasizes the need of repeated multidisciplinary team assessments and change of treatment intent if extraordinary responses are seen. The initial therapy consisted of short-course radiotherapy and surgery of the primary tumor followed by oxaliplatin-based combination chemotherapy and panitumumab with disease control intent. A complete radiologic response in >20 liver metastases in segments II–VIII was obtained. A biopsy-verified relapse of 3 liver metastases occurred at 9 months of treatment pause. Subsequently, major liver resection of 8 lesions was performed (4 with adenocarcinoma and 4 with cicatrix showing the challenge of disappearing lesions), followed by 6 months of adjuvant-like therapy. No relapse in MRI, PET, or CT has been noted since liver resection 6 years ago. Comprehensive genomic profiling of the primary tumor and liver metastases had similar driver mutations representing a low level of gene alteration and low diversity, possibly explaining the exceptional treatment response.